Expression and characterization of defensins from the hard tick Ixodes ricinus - Krátká, Julie (Jihočeská univerzita, 2022)
From Ixodes ricinus was extracted cDNA containing gene with a defensin. The defensin was cloned and expressed in modified E. coli bacteria. Results were analyzed via Western blot technique. Peptides used for testing of antibacterial activity were obtained from I. ricinus and added into borrelia cultures to observe their bactericidal effect against borrelia.
Expression and characterization of defensins from the hard tick Ixodes ricinus
Keywords: Ixodes ricinus; defensins; antimicrobial peptides; Borrelia; antibacterial activity; Ixodes ricinus; defensins; antimicrobial peptides; Borrelia; antibacterial activity